Beban Glikemik dan Aktivitas Fisik sebagai Faktor Risiko Kejadian Stunted Obesity pada Remaja Usia 16-18 Tahun di Kota Cirebon - Diah Yashinta, (2021)
Adolescents aged 16-18 years are of productive and active age and efforts to prevent obesity can still be done by monitoring diet and doing physical activity. Weight gain can be caused by the consumption of foods high on glycemic load and low levels of physical activity. This study aims to analyze glycemic load and physical activity as risk factors for the incidence of stunted obesity in adolescents aged 16-18 years in Cirebon City. The research method used was case control. There were 106 research respondents, consisting of 53 case groups (stunted obesity adolescents) and 53 control groups (stunted non-obesity adolescents) who lived in Cirebon City and met the inclusion criteria. The value of the glycemic load was obtained through interviews using the 24-hour food recal form and the level of physical activity was obtained by conducting interviews using the IPAQ (International Physical Activity Questionnaire) form. After processing and analyzing the data, the results obtained from the glycemic load as a risk factor for the incidence of stunted obesity (OR = 4.0; 1.75: 9.19) and physical activity as a risk factor for the incidence of stunted obesity (OR = 3.0; 1.36) : 6,70).